Parental Engagement to Promote a Reading Culture in the Tharu Community - Chaudhary, Tripti (Journal of Multidisciplinary Research Advancements, 2024)
This study adopted an ethnography approach to dig into the reading culture among parents of the public school in Kalilai district of Nepal. By examining the role of parents in creating a conducive reading environment at home and in school, the study aimed to highlight the impact of parental engagement on enhancing reading literacy and academic achievement. It looked into how parents of the Tharu community establish a reading culture in their homes. The findings underscore the crucial role of parents in nurturing a love for reading and strengthening children’s interest in education. The findings of the study show the crucial role of parental engagement in nurturing a love for reading and strengthening children’s interest in education within the Tharu community. The findings show the impact of parental involvement in creating a conducive reading environment at home and in school, emphasizing the significance of parental engagement in enhancing reading literacy and academic achievement. It is evident that parental participation, both home-based and school-based, plays a fundamental role in fostering a culture of reading and positively influencing students’ academic success. This research contributes to a better understanding of how parental engagement can effectively promote a reading culture within the Tharu community and potentially in other similar contexts.